Gouverner la vie privée: l'encadrement inégalitaire des séparations conjugales en France et au Québec - Biland, Émilie (Gouvernement en question(s), 2019)
"L'implication de l'État dans la vie privée pose problème : les individus ont davantage de droits que par le passé, mais certains de leurs comportements, jugés problématiques pour la collectivité, justifient un interventionnisme renouvelé, dans lequel acteurs privés et mécanismes de marché occupent une place croissante. En tension entre libéralisme et normalisation, cette action publique participe aux recompositions des rapports sociaux, entre les classes sociales, entre les genres, ainsi qu'entre la population majoritaire et les personnes racisées. Objet de vifs débats et de réformes récurrentes, la régulation par le droit des séparations conjugales est un observatoire précieux de ces recompositions, ici analysées à partir de trois enquêtes collectives, qualitatives et quantitatives, menées des deux côtés de l'Atlantique. En France comme au Québec, l'accès aux procédures, les interactions avec les professionnel.les et l'encadrement des modes de vie sont les trois dimensions constitutives du gouvernement de la vie privée. Cependant, chacun des contextes n'articule pas de la même manière inégalités de classe et inégalités de genre. En scrutant la production institutionnelle des inégalités privées, cet ouvrage invite à imaginer des voies alternatives, dans la sphère privée comme dans la sphère publique, pour que la politique des droits tienne ses promesses émancipatrices."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; droit des femmes*; droits des femmes*; europe; famille; france; hétérosexualité; inégalités; mariage; maternité; parentalité; patriarcat; premier cycle; privilèges; périodes historiques; québec; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexualité; soc2262; soc2264; sociologie; systèmes d'oppressions; séparation; thématiques

Une voix différente: la morale a-t-elle un sexe? - Gilligan, Carol; Kwiatek, Annick; Nurock, Vanessa; Laugier, Sandra; Paperman, Patricia; Brugère, Fabienne (Champs (Paris, France, 1977- ), 2019)
La morale a-t-elle un sexe ? Les femmes et les hommes ont-ils un sens différent de la moralité ? Une telle question donne la mesure de l’immense débat qu’a suscité le livre de Carol Gilligan, catalyseur des réflexions féministes sur une éthique qui valorise le souci des autres : le care. Aux États-Unis, Une voix différente est le texte le plus lu et le plus cité de la « deuxième vague » du féminisme. Il a ouvert un débat politique crucial, entre éthique de la justice et éthique du care, entre une moralité centrée sur l’équité, l’impartialité et l’autonomie et une moralité formulée « d’une voix différente », reconnue le plus souvent dans l’expérience des femmes, et fondée non sur des principes mais sur une question : comment faire, dans une situation donnée, pour préserver et entretenir les relations humaines qui sont en jeu ?
Keywords: amérique du nord; amériques; approches et analyses; cours; deuxième vague; discipline; discours dominant; patriarcat; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis; éthique

Bargaining with confucian patriarchy: Money, culture, and gender division of labor in Taiwanese immigrant families - Gu, Chien-Juh (Qualitative Sociology, 2019)
Previous studies of immigrant families have reported consistent findings concerning the positive effects of employed wives’ financial contributions and Western gender ideologies on women’s bargaining power in the family. This paper revisits this thesis. Data presented in this article are derived from a larger project based on 45 life-history interviews with Taiwanese immigrant women in a Midwest urban region. Findings suggest that women’s employment does not serve as a key factor that shapes spousal power relations in Taiwanese immigrant families. Rather, gendered work-family boundaries and individuals’ abilities construct main rationales in women’s interpretations of their division of labor at home and their dominance in financial management. None of the women interviewed consider Western culture as an inspiration for egalitarian gender ideology. In contrast, Confucian culture is often used by husbands and mothers-in-law to demand traditional gender practice, which is further reinforced and surveilled by the Taiwanese ethnic community. Therefore, the interconnections of work, family, money, culture, and power and their interactive effects on spousal relations are more complicated than previously suggested. This study also reveals varied forms of patriarchal bargaining in Taiwanese immigrant families. Married women tend to accommodate patriarchy in their housework assignment, but actively bargain in their management of family finances and persistence to seek employment. The findings suggest that heterogeneity within the research sample, household structure, and individuals’ subjectivities must be examined to understand the nuances and complexity of women’s gender strategies and bargaining power in immigration families. Theoretical implications of the study are also discussed.
Keywords: amériques; approches et analyses; asie; discipline; famille; femmes* immigrantes; patriarcat; projet charge mentale; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; taiwan; thématiques; travail; travail domestique; états-unis

Invisible labor and women’s double binds: Collusive femininity and masculine drinking in Russia - Utrata, Jennifer (Gender and Society, 2019)
The heavy drinking of alcohol remains primarily a hegemonically masculine ritual worldwide. Yet scholarship has undertheorized women’s practices in shaping the boundaries of masculine rituals, including drinking. Drawing on 12 months of ethnographic fieldwork and 151 interviews with single mothers, married mothers, nonresident fathers, and grandmothers from diverse class backgrounds, I demonstrate that Russian women perform extensive invisible management labor in attempting to produce responsible men. Constrained by a starkly unequal gender division of domestic labor, wives and mothers engage in varied “patriarchal bargains” as they shape men’s drinking practices, co-producing hegemonic masculinity. Whereas in the Soviet period women also managed men’s drinking, today new gender strategies have emerged. More women are held accountable to a collusive femininity involving both accommodation and resistance, upholding men’s drinking privileges only if breadwinning occurs. As women perform invisible labor, they end up reproducing the conditions that demand this labor from them in the first place. Some women embrace an alternative femininity by becoming single mothers and refusing to manage men’s drinking, especially when men fail as breadwinners. Theorizing collusive and alternative femininities, as well as women’s invisible labor, advances our knowledge of how multiple femininities shape, and may in time change, hegemonic masculinity. © 2019 by The Author(s).
Keywords: approches et analyses; asie; consommation d'alcool; discipline; hégémonie masculine; patriarcat; projet charge mentale; russie; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible